Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

I need help with this math question on my assignment

I Need Help With This Math Question On My Assignment class=

Sagot :

we have the expression

x^2+9x+20

Complete the square

equate the expression to zero

x^2+9x+20=0

group terms

(x^2+9x)=-20

x^2+9x+(9/2)^2-(9/2)^2=20

x^2+9x+(9/2)^2=20+(9/2)^2

Rewrite as perfect squares

(x+9/2)^2=-20+81/4

(x+9/2)^2=1/4

take square root on both sides

[tex](x+\frac{9}{2})=\pm\sqrt[]{\frac{1}{4}}[/tex]

simplify

[tex]\begin{gathered} x+\frac{9}{2}=\pm\frac{1}{2} \\ x=-\frac{9}{2}\pm\frac{1}{2} \end{gathered}[/tex]

the values of x are

x=-4 and x=-5

therefore

the given expression in factored form is

x^2+9x+20=(x+4)(x+5)

another way to find out the factored form

the formula to solve a quadratic equation of the form

ax^2+bx+c=0

[tex]x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}[/tex]

In this problem we have

x^2+9x+20=0

so

a=1

b=9

c=20

substitute in the formula

[tex]x=\frac{-9\pm\sqrt[]{9^2-4(1)(20)}}{2(1)}[/tex][tex]\begin{gathered} x=\frac{-9\pm\sqrt[]{1}}{2} \\ x=\frac{-9\pm1}{2} \\ x=\frac{-9+1}{2}=-4 \\ x=\frac{-9-1}{2}=-5 \end{gathered}[/tex]

the values of x are

x=-4 and x=-5

therefore

the factored form is

(x+4)(x+5)